Efficacy and safety of multimodal analgesic techniques for preventing chronic postsurgery pain under different surgical categories: a meta-analysis - Jun Zhou (Nature Portfolio, 2017)
Abstract The purpose of this meta-analysis was to compare the efficacy and safety of regional anesthesia to manage chronic postsurgery pain. A systematic search of PubMed, EmBase, and the Cochrane Central Register of Controlled Trials was performed to identify randomized controlled trials that focused on chronic pain frequency, analgesic consumption, and adverse effects under different surgical categories. We collected 21 trials assessing 1,980 patients for our meta-analysis. The summary of relative risks (RRs) and standard mean differences (SMDs) were calculated to measure the treatment effect of regional anesthesia. Results indicated that regional anesthesia significantly reduced the frequency of postsurgery pain (RR, 0.69; 95% confidence interval [CI], 0.56–0.85; p < 0.001). The results showed significant differences in overall patient satisfaction between applications with and without regional anesthesia (SMD, 1.95; 95%CI, 0.83–3.06; p = 0.001); however in other results, there were no significant differences between the two groups. Subgroup analysis suggested that regional anesthesia treatment might differ according to country. In conclusion, our study indicated that regional anesthesia was effective and safe in reducing the frequency of postsurgery pain and improved overall patient satisfaction; however, studies on the long-term efficacy and safety of regional anesthesia are still required to further confirm these findings.